Moderating Effects of Sharia Governance on Green Banking and Customer Loyalty in West Nusa Tenggara - Wulandari, Widya Rizki; Qoyyum, Abdul (Economica: Jurnal Ekonomi Islam, 2024)
The primary objective of this research is to examine the influence of green banking on green loyalty in Sharia banking in NTB, utilizing stakeholder theory, legitimacy theory, and self-regulation theory. The study expands on three key variables as a framework for understanding green banking: green innovation, green finance, and environmental performance. Additionally, it investigates the role of Sharia governance as a moderating factor in the relationship between green banking and green loyalty. Using quantitative methods and the SmartPLS 3.0 software for data analysis, this research reveals that both green innovation and environmental performance positively impact green loyalty, while green finance does not have a significant effect. Sharia governance was found to strengthen only the relationship between green innovation and green loyalty. The findings aim to contribute to the Sharia banking sector and encourage customers to choose environmentally friendly, sustainable products.